Study of solid-liquid extractions in a batch equipment - Escobedo F.A. (1998)
The author is grateful to Prof. F. Miranda (UNSA) and Prof. R. Gilbert (UNL) for helpful discussions, and to the reviewers of this manuscript for valuable comments. Partial financial support of CONCYTEC is gratefully acknowledged. Preliminary experimental work was performed in the laboratories of the Chemical Engineering Department of the Universidad Nacional de San Agustin (Peru).